Serious adverse drug reactions associated with anti-SARS-CoV-2 vaccines and their reporting trends in the EudraVigilance database - Wojciech Nazar; Jan Romantowski; Grzegorz Nazar; Marek Niedoszytko; Rüdiger Braun-Dullaeus; Ludmiła Daniłowicz-Szymanowicz (Scientific Reports)
Abstract A serious adverse reaction (SADR) may follow a vaccination against SARS-CoV-2 infection. We aimed to explore symptoms and reporting trends of SADRs to anti-SARS-CoV-2 vaccines based on the EudraVigilance database. This retrospective observational study analysed 250,966 suspected SADRs (with 62.8% reported in females), following the administration of 733,837,251 vaccine doses against SARS-CoV-2. Pfizer BioNTech (Comirnaty-Tozinameran), Moderna (Spikevax-Elastomeran), Janssen (Jcovden) and AstraZeneca (Vaxzevria) vaccines were analysed. The assessment included 897 types of SADRs across 12 categories. The most common clinical manifestations of SADRs to anti-SARS-CoV-2 vaccines vaccines encompassed neuropsychiatric (n = 121,877), cardiovascular (n = 78,167), as well as musculoskeletal and connective tissue disorders (n = 63,994). After summarising all SADRs, vaccination with Comirnaty was associated with the lowest risk of experiencing SADRs (754/million administered doses), followed by Spikevax (785/million doses), Jcovden (1,248/million doses) and Vaxzevria (2,301/million doses; p < 0.001). Regarding the vaccine administration timelines, the reporting of SADRs tends to be delayed and occurs over a longer time (p < 0.001). SADRs associated with anti-SARS-CoV-2 vaccines seem to be relatively rare. Compared to adenovirus-based vector vaccines (Jcovden, Vaxzevria), mRNA vaccines appear to offer improved safety profiles (Comirnaty, Spikevax). The risk of SADR to any SARS-CoV-2 vaccine seems to be outweighed by the benefits of active immunization against the virus.